The Impact of Health Education Training on Knowledge of Prevention and Control of Hypertension among Youth Group - Fitriadi, Yogi; Fajri, Imam Khoirul; Pramantara, I Dewa Putu (Review of Primary Care Practice and Education, 2024)
Introduction: Hypertension is a serious issue that can lead to various complications if not prevented and managed, starting from adolescence and young adulthood. Education on non-communicable diseases related to hypertension has been limited in schools, with little focus on community settings. This study aims to examine the impact of health education for adolescents and young adults on changes in knowledge and behavioral practices for the prevention and control of hypertension. Methods: This study employs a quasi-experimental design with pretest and posttest without a control group. Subjects were obtained through purposive sampling, resulting in a total of 32 respondents. Demographic characteristics and Kirkpatrick Level I evaluations were analyzed univariately. The comparison of knowledge scores before and after the intervention was analyzed bivariate, taking data normality into account. Results: After receiving health education for adolescents and young adults, there was a significant increase in knowledge scores regarding hypertension prevention and control before and after the intervention (p<0.001). The evaluation of the training program yielded very good scores, with the highest percentage from the facilitator evaluations. Conclusion: There was an increase in knowledge scores related to hypertension prevention and control among adolescents and young adults after receiving health education interventions from health professionals.